2019
DOI: 10.2217/rme-2019-0009
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Inflammation in Wounds of Diabetic Patients Treated with Porcine Urinary Bladder Matrix

Abstract: Aim:To determine if porcine urinary bladder matrix (UBM) treatment is associated with modulation of wound inflammation in diabetic patients.Patients & methods:mRNA associated with M1 and M2 macrophages were measured in wounds of diabetic and nondiabetic patients pre- and post-treatment with UBM and an M1:M2 score was calculated.Results:Wound tissue from diabetic subjects exhibited elevated M1:M2 scores compared with nondiabetic patients, suggesting a greater pro-inflammatory state prior to treatment. Post-trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…Although the full contributory role of ADMs in DFUs has not yet been elucidated, the mechanistic effects of specific proprietary ADMs has been witnessed. In one study, application of a xenogenic ADM was able to return the M1:M2 macrophage polarization ratio normally seen in DFUs to that of normally-healing wounds [ 97 ]. Furthermore, ADMs have also been witnessed to induce increased levels of microvascular blood flow within DFUs [ 98 ].…”
Section: Acellular Dermal Matricesmentioning
confidence: 99%
“…Although the full contributory role of ADMs in DFUs has not yet been elucidated, the mechanistic effects of specific proprietary ADMs has been witnessed. In one study, application of a xenogenic ADM was able to return the M1:M2 macrophage polarization ratio normally seen in DFUs to that of normally-healing wounds [ 97 ]. Furthermore, ADMs have also been witnessed to induce increased levels of microvascular blood flow within DFUs [ 98 ].…”
Section: Acellular Dermal Matricesmentioning
confidence: 99%
“…DM2 has been shown to modulate the macrophage phenotype and increase the ratio of pro-and anti-inflammatory macrophages [17] . However, glycation has been shown to modulate the macrophage phenotype against the anti-inflammatory state in the long term [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…AlloDerm ® showed that the macrophages were mostly M1 at 7, 14, 21, and 42 days post implantation, while Integra ® showed a mixed M1/M2 population of macrophages at all time-points: The trend for the M1:M2 ratio was skewed towards M2 on day 7, towards M1 on days 14 to 21, and again towards M2 on day 42 for Integra ® [156]. A recent study showed that the implant of a porcine urinary bladder matrix (UBM) is associated with the modulation of wound inflammation in diabetic patients, measured as mRNA associated with M1 and M2 macrophages [157]. Recently, Montanaro et al show investigate how the dermal substitute Nevelia ® , which is a dermal substitute consisting of a three-dimensional porous matrix of type 1; purified, stabilized, bovine-origin collagen; and a layer of reinforced silicone may influence the inflammatory infiltrate and macrophages polarization [158].…”
Section: Dermal Substitutesmentioning
confidence: 98%